2018
DOI: 10.7759/cureus.2854
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Gastric Gastrointestinal Stromal Tumor in a Patient with Neurofibromatosis

Abstract: Neurofibromatosis type 1 is an autosomal dominant neurocutaneous disorder characterized by a mutation of the neurofibromin 1 (NF1) gene, resulting in increased susceptibility for multiple tumors, namely, gastrointestinal stromal tumors (GISTs)—the most common types of mesenchymal neoplasms in the gastrointestinal tract. Despite these tumors' predilection for the stomach, it seems to be the least likely part of the gastrointestinal (GI) tract to be affected in cases of neurofibromatosis. Herein, we report a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Surgical resection is a commonly used treatment modality for bleeding GISTs, while other options include adjuvant and neo-adjuvant Imatinib, a tyrosine kinase inhibitor [6,13,14]. Benjamin et al showed increased survival with surgical resection compared to chemotherapy alone [15].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is a commonly used treatment modality for bleeding GISTs, while other options include adjuvant and neo-adjuvant Imatinib, a tyrosine kinase inhibitor [6,13,14]. Benjamin et al showed increased survival with surgical resection compared to chemotherapy alone [15].…”
Section: Discussionmentioning
confidence: 99%
“…The birth incidence is estimated to be 1:3000 via autosomal dominant transmission[5]. The underlying pathogenesis is thought to be based on biallelic loss of the NF-1 tumor suppressor gene that leads to loss of neurofibromin, a negative regulator of RAS signaling[6].…”
Section: Discussionmentioning
confidence: 99%
“…No recurrences or metastases were found after long-term follow-up, but there are a few exceptions. Momani et al[6] reported a recurrent GIST in a patient with neurofibromatosis. The tumor cells from our two cases were well differentiated and low proliferative activity, and tumors were small in size.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate was reported to be highest in young adulthood, between ages 15 and 30 years [4]. In addition, a previous case report highlighted the ability of NF1-associated GISTs to recur throughout a patient's life [14]. This, along with the mortality rate being higher in younger adults with NF1-associated GISTs, makes detecting the tumor in younger patients even more crucial.…”
Section: Discussionmentioning
confidence: 99%